Consideration of Two Cases of Ascending Aortic Dissection That Began with Stroke-Like Symptoms - Chiaki Takahashi (Case Reports in Neurological Medicine, 2015)
We recently experienced two patients with stroke-like symptoms and ascending aortic dissection (AAD) in our outpatient department. Both patients were transferred to our hospital presenting with neurological deficit such as hemiparesis and conjugate deviation. They did not complain from any chest or abdominal pain. Their MRI did not show fresh infarction or main branch occlusion. A chest CT image showed AAD. The former patient was immediately transferred to a tertiary hospital and the latter received conservative management in the cardiovascular department. Discussion. As neither patient was experiencing any pain, we initially diagnosed them with ischemic stroke and began treatment. Fortunately, bleeding complications did not occur. In such cases, problems are caused when intravenous tissue plasminogen activator (t-PA) injection is administered with the aim of reopening the occluded intracranial arteries. In fact, patients with AAD undergoing t-PA injection have been reported to die from bleeding complications without any recognition of the dissection. These findings suggest that confirmation using carotid ultrasound, carotid MR angiography, and a D-dimer test is crucial and should be adopted in emergency departments.